Photo-triggered C-arylation of active-methylene compounds with diazonium salts via an electron donor-acceptor (EDA) complex - Pandey S.; Kamal A.; Kushwaha A.K.; Singh H.K.; Maury S.K.; Singh S. (My University, 2025)
The elucidation of the C-arylation of active methylene compounds under visible light conditions without a photocatalyst presents an intellectual challenge. The photo-induced C-arylation of active methylene compounds via electron donor-acceptor (EDA) complexes shows a strategic path for the synthesis of pharmacologically relevant compounds. This expansive and efficacious methodology facilitates C-arylation under environmentally conscientious conditions, exhibiting exemplary compatibility with diverse functional groups and yielding numerous compounds. This environmentally sustainable transformation underscores the merits of the procedural simplicity and benign reaction conditions. Notably, all resultant products were judiciously derived from active methylene compounds and diazonium salts through the intermediacy of the EDA complex. © 2024 The Royal Society of Chemistry